EVALUATION OF CNS DEPRESSANT AND BEHAVIORAL ACTIVITY OF AN ETHANOL EXTRACT OF ZIZIPHUS JUJUBA (BER) IN MOUSE MODEL - UPADHYAY, SUKIRTI; KUMAR, BHASKAR; UPADHYAY, PRASHANT (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: Ziziphus jujuba, known as Ber (Hindi), is an indigenous herb found in India. Z. jujuba has been used to treat various diseases such as respiratory system diseases (asthma, cough, and laryngitis), gastrointestinal problems (constipation, colitis, and liver diseases), as well as cardiovascular and genitourinary system diseases. Seeds and fruit have been also reported to have central nervous system (CNS) depressant effect. Hence, in this study, neuropharmacological effects of leaves are studied which are not reported previously. Z. jujuba extract’s potential to depress the CNS and affect behavior was examined in this study, along with the phytochemicals that may be responsible for these effects. Methods: 400 mg/kg of the extract was administered intraperitoneally. As a benchmark, diazepam (2 mg/kg body weight i.p.) was used. ANOVA and Dunnett’s tests were used to evaluate the data. The results were all presented as Mean (SEM) values. p>0.05 was regarded as meaningful. Result: The outcome of the study demonstrated that ethanol extract of Z. jujuba (400 mg/kg i.p.) reduced locomotion, caused muscle relaxation, and had anti-anxiety effects. Conclusions: Ethanols extract of Z. jujuba leaves exhibits CNS depressant action and significant anxiolytic activity comparable to diazepam.